Hot electron transfer in Zn–Ag–In–Te nanocrystal–methyl viologen complexes enhanced with higher-energy photon excitation. Issue 28 (24th April 2020) - Kameyama, Tatsuya; Sugiura, Kouta; Kuwabata, Susumu; Okuhata, Tomoki; Tamai, Naoto; Torimoto, Tsukasa
Abstract : Zn–Ag–In–Te nanocrystals exhibited hot electron transfer to adsorbed methyl viologen, the efficiency being enhanced from 45% to 72% with an increase in the excitation photon energy. Abstract : The dynamics of hot electron transfer from Zn–Ag–In–Te (ZAITe) nanocrystals (NCs) to adsorbed methyl viologen (MV 2+ ) were investigated by transient absorption spectroscopy. The bleaching of the exciton peak in the ZAITe NC–MV 2+ complexes evolved faster than that of ZAITe NCs. The hot electron transfer efficiency increased from 45% to 72% with increasing excitation photon energy.